Effects of ketone monoester and bicarbonate co-ingestion on cycling performance in WorldTour cyclists - Ramos-Campo, D. J.; López-Román, F. J.; Pérez-Piñero, S.; Ortolano, R.; Abellán-Ruiz, M. S.; Molina Pérez de los Cobos, E.; Luque-Rubia, A. J.; Van Elslande, D.; Ávila-Gandía, V. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
The present randomized study investigated the effect of acute supplementation of 800 mg/kg of ketone monoester ingestion (KE) or placebo (PL) and 210 mg/kg of NaHCO3 co-ingestion on cycling performance of WorldTour cyclists during a road cycling stage simulation. Twenty-eight cyclists participated in the study (27.46 ± 4.32 years; 1.80 ± 0.06 m; 69.74 ± 6.36 kg). Performance, physiological, biochemical, and metabolism outcomes, gut discomfort, and effort perceived were assessed during a road cycling simulation composed of an 8-min time-trial (TT) performance + 30-s TT + 4.5 hr of outdoor cycling + a second 8-min TT + a second 30-s TT. Greater absolute and relative mean power during the first 8-min TT (F = 5.067, p = .033, n²_p =.163, F = 5.339, p = .029, n²_p = .170, respectively) was observed after KE than after PL (KE: 389 ± 34, PL: 378 ± 44 W, p = .002, d = 0.294 and KE: 5.60 ± 0.42, PL: 5.41 ± 0.44 W/kg, p = .001, d = 0.442). Additionally, greater concentration of ß-hydroxybutyrate blood concentration (F = 42.195, p < .001, n²_p = .619) was observed after KE than after PL during the first steps of the stage (e.g., after warm-up KE: 1.223 ± 0.642, PL: 0.044 ± 0.058 mM, p < .001, d = 2.589), although the concentrations returned to near baseline after 4.5 hr of outdoor cycling. Moreover, higher values of anion gap were observed (F = 2.333, p = .026, n²_p = .080) after KE than after PL ingestion, after the warm-up and after the first 8-min and 30-s TT. Additionally, lower concentrations of HCO3- were reported in the KE condition after warm-up and after the first 8-min and 30-s TT. During the initial phase of the stage simulation, acute supplementation with KE + NaHCO3 co-ingestion enhanced 8-min TT cycling performance (3.1%) in WorldTour cyclists with a concomitant hyperketonaemia.